1982
DOI: 10.1107/s0567740882007729
|View full text |Cite
|
Sign up to set email alerts
|

Structure of 1-fluoroadamantane, C10H15F, in its plastic phase

Abstract: Single-crystal X-ray diffraction data were collected and interpreted for the plastic phase of 1-fluoroadamantane, C10H15 F at 293K. The unit cell is face-centred cubic with a = 9.535 (4)A, space group Fm3m, Z = 4. On the assumption of a rigid molecular skeleton, several types of orientational disorder were investigated: hindered reorientations between equally weighted orientations, free uniaxial rotation of the molecules about the C-F axis and decomposition of the atomic orientational average density on symmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 8 publications
1
30
0
Order By: Relevance
“…We find for ethanol five bcc space groups which fulfil these conditions, namely, I23, Im3 ͑m3 Laue class͒ and I432, I43m, Im3m ͑m3m Laue class͒. Between those, as experience dictates [21][22][23] the space group most likely to provide a faithful representation of the OG and RP structures is the one with the maximum allowed symmetry within the Laue class. This property stems from the high entropy arising from dynamical disorder characteristic of plastic ͑rotator͒ crystals, and hence the space group must generate a large number of symmetryequivalent molecular orientations.…”
mentioning
confidence: 80%
“…We find for ethanol five bcc space groups which fulfil these conditions, namely, I23, Im3 ͑m3 Laue class͒ and I432, I43m, Im3m ͑m3m Laue class͒. Between those, as experience dictates [21][22][23] the space group most likely to provide a faithful representation of the OG and RP structures is the one with the maximum allowed symmetry within the Laue class. This property stems from the high entropy arising from dynamical disorder characteristic of plastic ͑rotator͒ crystals, and hence the space group must generate a large number of symmetryequivalent molecular orientations.…”
mentioning
confidence: 80%
“…34 It was shown that the fluorine atom occupies 8 distinguishable equilibrium positions corresponding to so as many orientations along the [111] direction of the cubic lattice in such a way that the threefold molecular and crystal axes are coincident. 31 The relaxation observed with dielectric spectroscopy was assigned to jumps of the molecular dipole between neighboring [111] directions of the cubic lattice. 29 Incoherent quasielastic neutron scattering measurements showed the existence of two characteristic correlation times, corresponding one to the dipolar tumbling observed by dielectric spectroscopy and the other to uniaxial 120 o rotations between three equilibrium positions around the molecular symmetry axis (along the C-F dipole direction).…”
Section: Introductionmentioning
confidence: 99%
“…The disordered phases of these adamantanes belon to the same space group, Fm3m, Z = 4, where r = 9.445 1 for adamantane (29). and o = 9.53 A for fluoroadamantane (7). From these unit cell dimensions, the densities of these solids are calculated to be 1.07 and 1.18 g crnp3, respectively.…”
Section: Ch2 Scissormentioning
confidence: 99%
“…The melting temperature in a sealed tube was measured to be 525 K, but the entropy of fusion was not measured. Single-crystal X-ray diffraction (7) 'Authors to whom correspondence may be addressed. was used to determine the structure of the high-temperature phase as face-centred cubic (FmSm), with four molecules per unit cell, with a = 9.535 (4) A.…”
Section: Introductionmentioning
confidence: 99%